1996
DOI: 10.1017/s0021859600078023
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of digestion in cattle fed sugarcane: prediction of nutrient supply for milk production with locally available supplements

Abstract: S U M M A R YA previously described model of digestion in cattle fed sugarcane diets was applied to predict nutrient supply to the host animal from dietary intake, to indicate pre-experimentally the suitability of various supplements to enhance the milk production of dairy cattle in the tropics fed sugarcane-based diets. Potential milk production was calculated according to simulated energy and lipogenic, glucogenic and aminogenic nutrient availability. The addition of small amounts of urea (10 g/kg sugarcane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…However, several studies reported lower milk yield for cows fed WSC relative to those fed other tropical forages (Alvarez and Preston 1976;Alvarez et al 1978;Paiva et al 1991). Using digestion models, Dijkstra et al (1996) and Kebreab et al (2001) suggested that low availability of amino acids is probably the factor that a Urea was applied at the rate of 50 g kg -1 , dry matter basis most severely limits milk production by dairy cows fed unsupplemented WSC diets. Other less limiting factors are energy and long chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies reported lower milk yield for cows fed WSC relative to those fed other tropical forages (Alvarez and Preston 1976;Alvarez et al 1978;Paiva et al 1991). Using digestion models, Dijkstra et al (1996) and Kebreab et al (2001) suggested that low availability of amino acids is probably the factor that a Urea was applied at the rate of 50 g kg -1 , dry matter basis most severely limits milk production by dairy cows fed unsupplemented WSC diets. Other less limiting factors are energy and long chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…However, milk yield of cows fed sugarcane was generally lower than that of cows fed other forages (Preston 1988). Limited supplies of absorbed amino acids and energy are likely the reasons for the low productivity of cows fed sugarcane (Dijkstra et al 1996;Kebreab et al 2001). Supplementation with other tropical legumes such as Leucaena leucocephala increased milk yield of cows fed sugarcane-based diets (Alvarez and Preston 1976;Alvarez et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Positive AV differences and uptakes indicate metabolite removal from plasma, whereas negative values indicate net metabolite release from the mammary glands. Mammary gland nutrient balances were calculated using mean milk protein AA composition reported by Mepham (1987) and Lapierre et al (2012) for AA uptake: output ratios (U:O) and according to estimations of Dijkstra et al (1996) for glucose, 2C compounds (acetate and BHB), and LCFA. Of C16 FA in milk, 50% were assumed to be synthesized de novo from 2C compounds and 50% were assumed to be sequestered as preformed FA.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Overall, the mammary gland sequestered glucose in excess of estimated requirements for lactose and fat synthesis, assuming that 1.05 and 0.31 g of glucose is required to synthesize 1 g of lactose and fat, respectively (Dijkstra et al, 1996). On average across all diets, 61% of glucose uptake contributed to lactose synthesis.…”
Section: Mammary Glucose Balancementioning
confidence: 99%
“…Fatty acid fractions include long chain fatty acids (Ld) and volatile fatty acids (Va) and, the rumen microbial DM (Mi) is represented by one state variable. Detailed description of the model and applications are described in Dijkstra et al (1996a;1996b).…”
Section: Model Modificationsmentioning
confidence: 99%